1983
DOI: 10.1021/bi00294a001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3.beta.-[2-(diethylamino)ethoxy]androst-5-en-17-one on the synthesis of cholesterol and ubiquinone in rat intestinal epithelial cell cultures

Abstract: The relationship between cholesterol and ubiquinone synthesis in rat intestinal epithelial cell cultures was examined by using 3 beta-[2-(diethylamino)ethoxy]androst-5-en-17-one hydrochloride (U18666A). Addition of U18666A to cells caused a greater than 90% inhibition of incorporation of [3H]acetate into cholesterol and an apparent large increase in the incorporation of [3H]acetate and [3H]mevalonate into ubiquinone. However, the incorporation of 4-hydroxy[U-14C]benzoate, a ring precursor of ubiquinone, was un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 28 publications
(30 reference statements)
2
48
1
Order By: Relevance
“…In CHO cells, GW707 is approximately 10-fold less potent than U18666A with respect to inhibition of LDL-stimulated cholesterol esterification, whereas in HepG2 cells, GW707 is 2-to 3-fold more potent than U18666A in inhibition of cholesteryl ester synthesis (E. Lopez-Perez and M. Issandou, unpublished data). In addition, U18666A, unlike GW707, impairs cholesterol biosynthesis through the inhibition of 2,3-oxidosqualene cyclase (30). In the present study, we found that GW707 does not significantly affect the synthesis of 25-HC in response to LDL cholesterol, whereas U18666A-treated cells exhibit a 40% reduction in the rate of secretion of 25-HC.…”
Section: Downloaded Fromcontrasting
confidence: 45%
“…In CHO cells, GW707 is approximately 10-fold less potent than U18666A with respect to inhibition of LDL-stimulated cholesterol esterification, whereas in HepG2 cells, GW707 is 2-to 3-fold more potent than U18666A in inhibition of cholesteryl ester synthesis (E. Lopez-Perez and M. Issandou, unpublished data). In addition, U18666A, unlike GW707, impairs cholesterol biosynthesis through the inhibition of 2,3-oxidosqualene cyclase (30). In the present study, we found that GW707 does not significantly affect the synthesis of 25-HC in response to LDL cholesterol, whereas U18666A-treated cells exhibit a 40% reduction in the rate of secretion of 25-HC.…”
Section: Downloaded Fromcontrasting
confidence: 45%
“…In addition to its effect on the accumulation of cholesterol in late endosomes/lysosomes, U18666A is reported to inhibit oxidosqualene cyclase, an intermediate step in cholesterol synthesis ( 25 ). Inhibition of this enzyme led to the generation of 2,3-monoepoxysqualene and 2,3;22,23-diepoxysqualene, two substrates of oxydosqualene cyclase ( 38,44,45 ). Our results suggest that compounds 5 and 10 inhibit oxidosqualene cyclase.…”
Section: Resultsmentioning
confidence: 69%
“…Proteins were solubilized with CHAPS, separated by size exclusion chromatography, and the elution profile of Bax was analyzed by immunoblotting. For each condition, even-numbered fractions were loaded on two separate gels; a short exposure time was chosen for the low molecular weight fractions (30-44), and a longer one for the high molecular weight fractions (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) and its sensitivity to trypsin digestion were analyzed by immunoblotting. The presence of tBid was required for the recruitment of Bax to liposomes and led to the appearance of a Tr-Bax fragment (Figure 1d).…”
Section: Resultsmentioning
confidence: 99%
“…It interferes with the trafficking of cholesterol, causing its increase in late endosomes/lysosomes, 23,24 and inhibits its neosynthesis in the ER. 25 A recent study reported the accumulation of cholesterol in the mitochondria of neurons isolated from an Niemann-Pick Type C1 mouse model, 26 raising the possibility that U18666A might also increase mitochondrial cholesterol content. We therefore incubated HeLa cells with U18666A, isolated mitochondria, and analyzed their lipid composition by thin-layer chromatography (Figure 3a and b).…”
Section: Resultsmentioning
confidence: 99%